Drawing from a Deeper Well: Contemplative Asian Sources of Radical Existential Thought (Existential Analysis: Journal of the Society for Existential Analysis, 2017)
This paper discusses how Taoism and Buddhism are significant, if unrecognized, sources of what we think of as Existential thought. The radical philosophies of Buber and Heidegger are discussed as essential examples that have been inspired and informed by Asian non-dualistic traditions. This intellectual heritage expands the Euro-centrism of Existential thought into a necessarily, and potentially creative, East/West philosophy, and challenges Existential Therapy to recognize itself as a fundamentally contemplative discipline that must rethink its understanding of authenticity.
Keywords: Existential Therapy; East/West Psychology; Heidegger; Buber; Buddhism; Taoism; nonduality; authenticity